Application of a modified Neff classification to patients with uncomplicated diverticulitis. (November 2013) - Mora Lopez, L.; Serra Pla, S.; Serra‐Aracil, X.; Ballesteros, E.; Navarro, S.
Abstract Aim Severity of acute diverticulitis (AD) has traditionally been assessed using the Hinchey classification; however, this classification is predominantly a surgical one. The Neff classification provides an alternative classification based on CT findings. The aim of this study was to evaluate a modification of the Neff classification to select patients presenting with early‐stage AD to receive outpatient management. Method All patients with AD, presenting to a single unit, were prospectively studied. All patients underwent emergency abdominal CT and were assigned a Neff stage, including a modification (mNeff) to Neff Stage I. The Neff stages used were: Stage 0, uncomplicated diverticulitis; Diverticula, thickening of the wall, increased density of the pericolic fat; Stage I, locally complicated (our modification included substages Ia (localized pneumoperitoneum in the form of air bubbles) and Ib (local abscess); Stage II, complicated with pelvic abscess; Stage III, complicated with distant abscess; and Stage IV, complicated with other distant complications. Patients who presented with Stage 0 or Stage Ia were selectively managed as outpatients. Patients with comorbidity or the presence of the systemic inflammatory response syndrome (SIRS) were excluded. Results Between February 2010 and January 2013, 205 patients (mean age 59 years; age range 25–90 years) presented with AD. One‐hundred and forty‐nine met the radiological criteria for potential outpatient treatment. After applying the exclusion criteria, 68 were eventually assigned to an outpatient programme. Sixty‐four (94%) successfully completed the outpatient treatment protocol; four patients were readmitted. Conclusion Our mNeff classification allowed selected patients with AD to be successfully managed in an outpatient programme.